Evaluation of Infancy Vaccine Applications within the Scope of Custodial Right - Seda İrem Çakırca Yüceoğlu (İstanbul Hukuk Mecmuası)
Vaccine hesitation, described by theWHOas “delay orrefusal in the acceptance of vaccines notwithstanding the availability of vaccine services” and vaccine refusal, defined as the rejection of all vaccines, have been documented in more than 90% of the world’s countries. In Turkey, some parents are increasingly rejecting vaccination of infants. These vaccines are essential to prevent the emergence of preventable diseases, especially in infants, and to prevent deaths caused by these diseases. The discussion of making vaccinations compulsory after the Covid-19 pandemic made it important to reexamine the necessity of infancy vaccinations. In its Halime Sare Aysal decision regarding infancy vaccination in 2015, the Constitutional Court found legal representatives of infants who refuse to consent to infancy vaccination practices to be a violation of rights. However, contrary to the Constitutional Court decision’s reasoning, when the issue of whether to give consent that will make the medical intervention lawful is taken into consideration within the framework of the scope of limitation of the right of custody and “best interests of the child,” mandatory vaccination debates will cease to be a typical constitutional law debate. In the first part of this study, the regulation of infancy vaccination practices in comparative law will be discussed. Furthermore, in the second part, the legislation regarding infancy vaccination practices in Turkey and the position of the national and supranational judiciary will be examined. In the last part, the refusal of the legal representative of the infant to consent to medical intervention will be analyzed in the context of limiting or removing the right of custody on the basis of the best interests of the child.